Modelling the Neolithic Transition in the Near East and Europe. Issue 2 (20th April 2012) - Fort, Joaquim; Pujol, Toni; Linden, Marc Vander
Abstract: For the Neolithic transition in the Near East and Europe, this paper compares the isochrones predicted by computational models to those obtained by interpolating the archaeological data. This comparison reveals that there is a major inconsistency between the predictions of the models and the archaeological data: according to the models, the Neolithic front would have arrived to Greece in less than half the time interval implied by the data. Our main new results are as follows, (a) This inconsistency can be solved by including only Pre Pottery Neolithic B/C (PPNB/C) sites in the Near East; (b) the model that yields the lowest mean error per site in the arrival time of the Neolithic across the Near East and Europe is obtained by allowing for sea travels up to distances of 150 km; and (c) Mountain barriers have a negligible effect on the spread rate of the Neolithic front at the continental scale.